HEDGING IN ACADEMIC WRITTEN DISCOURSE - Nuan Ifga; Indra Pratiwi (Pusat Riset dan Inovasi Nasional, 2021)
The recent proliferation of studies on hedging in written academic discourse shows that hedging has been widely employed and is considered effective and a prerequisite for scientific journals. Hedging is generally used for making a proposition and its relationship with the representation of reality and for attenuating the claims to avoid any risks of negations. The present research analyses the use of hedging in the Indonesian academic context. The data were taken from a corpus, named C-Smile, of undergraduate students’ theses of the English Department, Faculty of Letters, State University of Malang, totaling up to 1,587,059 words. Employing the hedging taxonomy advocated by Hyland (1996), the present project discovers that “reliability” hedges were the most frequent (88.13%) in use. Of the reliability hedges, modal verbs were found to have the highest frequency (79.60%). Furthermore, the modal auxiliary verb ‘can’ was the most frequently occurring hedging device (38.94%). Nevertheless, there is a scarce occurrence of highly-technical terms of hedges, such as allegedly, presumably, supposedly, etc. Moreover, hedges were more frequent in the Discussion section (56.74%) than in the Introduction section (43.26%). It was concluded that they mostly employ reliability hedges referring to the not-feel-confident due to the influence of culture, i.e., collectivism. It is also possible that they use hedges for the sake of politeness and to make their claims accepted by the readers (Bonyadi et al., 2012). Additionally, the typical kinds of hedges employed and (mis)use of hedges may be attributed to the fact that the corpus is the product of EFL learners whose English falls into the category of interlanguage.